PEMANFAATAN JAHE MERAH SEBAGAI PENGUATAN KETAHANAN EKONOMI MASYARAKAT MELALUI PEMBERDAYAAN UMKM - Ari Yudha Caesar Sutikno; Fathin Aulia Rahman (Jurnal Padamu Negeri, 2025)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth Economic resilience is one of the fundamental aspects of sustainable development that targets the community's ability to maintain and improve its standard of living independently. Based on Law No. 20 of 2008, MSMEs have a major role in labor absorption and contribution to national GDP. MSMEs also act as a means of community empowerment, alleviating poverty, and creating economic equity. the development of traditional herbal products based on red ginger is a promising opportunity. One of the innovations developed is red ginger powder, which not only has health benefits but also high economic value. The method used in this community service activity is through participatory and collaborative methods. The utilization of red ginger as the main ingredient of herbal products has had a significant impact in strengthening the economic resilience of the community. Through the empowerment of MSMEs and the development of red ginger powder products, new business opportunities, increased income, and awareness of healthy consumption in the community were created.